Effect of Magnetichydrodynamic on unsteady flow and heat transfer upon stretching sheet with non – uniform heat - Ibrahim, Tagreed; Hadi, Ahmed (Iraqi Journal of Science, 2023)
In this paper we study the effect of magnetichydrodynamic upon the boundarylayer flow and heat transfer on a permeable unsteady stretching sheet with non –uniform heat source / sink. It found that the momentum and energy equations arecontrolled by many different dimensionless parameters such as prandtle numberpr , unsteadiness parameter A , constant pressure So , coefficient of the spacedependent  A , the temperature dependent  B , and the MHD parameter M . Theanalytic solutions are obtained by using suitable similarity transformations andhomotopy analysis method (HAM).Furthermore, we analysis the effects of all dimensionless number, there arementioned above, upon the velocity distribution and hest transfer distribution. Thisstudy is done through plotting (36) graph by using the Mathematica package.